Synergistic effects of recycled concrete powder, GGBFS, and basalt fibers on mechanical and durability performance of recycled aggregate concrete - Alaa Taha (17302783) (2024)
This study investigates the sustainable utilization of construction and demolition waste (CDW), specifically recycled concrete powder (RCP), as a partial substitute for cement in concrete. It evaluates the combined effects of basalt fibers (BF) and ground granulated blast furnace slag (GGBFS) on the mechanical and durability properties of recycled aggregate concrete (RAC) incorporating RCP over different curing durations. The study included aggregate and binder characterization tests, along with examining concrete properties, considering parameters such as aggregate type (100 % natural gabbro aggregates (NGA) and 50 % recycled concrete aggregates (RCA)-50 % NGA), binder composition (unary, binary, and ternary blends), and BF addition (0 % and 0.75 % by volume fraction ( Vf )). The mechanical properties of concrete were evaluated through compressive strength and flexural properties. Additionally, physical properties such as water absorption, density, and porosity were examined. Durability properties were also evaluated, including the rapid chloride penetration test (RCPT) and surface electrical resistivity (SER). Scanning electron microscopy (SEM) analysis was performed to examine the microstructure of the tested concrete mixes. Test results indicated that the addition of 0.75 % BF to ternary blended RAC with 15 % RCP, 30 % GGBFS, and 55 % ordinary Portland cement (OPC) effectively offset compressive strength reductions, aligning it with the compressive strength of 100 % OPC-based RAC, both with and without BF. Additionally, this mix exhibited a 10.0 % higher flexural tensile strength, a 21.4 % lower charge passing based on RCPT, and a 97.2 % higher SER when compared to 100 % OPC-based RAC with BF. Moreover, the combined effect of incorporating BF and supplementary cementitious materials (SCMs), RCP and GGBFS, yielded superior enhancements in both strength and durability compared to the individual contributions of BF or SCMs when used alone. Other Information Published in: Structures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.istruc.2024.108058